Voltammetric behaviour and quantitative determination of pesticide iminoctadine - Smarzewska, Sylwia; Metelka, Radovan; Guziejewski, Dariusz; Skowron, Monika; Skrzypek, Slawomira; Brycht, Mariola; Ciesielski, Witold (Royal Society of Chemistry, 2014)
Iminoctadine (IOD) was determined in spiked river water samples by square wave voltammetry (SWV) using a cyclic renewable silver amalgam film electrode (Hg(Ag)FE). It was found that the compound can act as an electrocatalyst. In Britton–Robinson buffer at pH 6.5 a signal connected with the catalytic hydrogen evolution reaction was detected at −1.8 V versus Ag/AgCl. Validation of the method was carried out. The LOD and LOQ have been estimated to be 2.6 × 10−9 mol L−1 and 8.5 × 10−9 mol L−1, respectively.